Perancangan Media Informasi Tari Sekapur Sirih Jambi dalam Bentuk Buku Ilustrasi - Ramli Syahrul Muharam; Harissman Harissman; Anin Ditto; Olvyanda Ariesta (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Sekapur Sirih Dance is a traditional dance used to welcome important guests in Jambi Province. However, unfortunately many Jambi people, especially teenagers, only know this dance as a form of welcoming, without understanding more deeply about the history, meaning, movements, properties, values, and philosophy contained in it. Therefore, designing an illustrated book about Sekapur Sirih Dance can be an effective means to disseminate information and introduce this dance culture to teenagers and the wider community. The illustrated book comes with a dynamic and colorful design to introduce various aspects of Sekapur Sirih Dance. The method used in this design is the 5W + 1H analysis, which includes questions about what needs to be conveyed, who the target audience is, where this information will be disseminated, when this problem arises, why it is important, and how to attract the attention of teenagers with an appropriate approach. The design process includes interviews, field observations, library data collection, direct surveys to schools, and documentation. The stages of creating the work consist of brainstorming, sketching, story writing, color studies, typography, and storyboards. The final results of this design are illustrated books, e-books, posters, x-banners, stickers, pins, and key chains.